The Iglesia Filipino Independiente (IFI) in Antique 1898-1906 - Talledo, Tomasito T. (Danyag : Journal of Humanities and Social Sciences, 1998)
The Philippine revolution against Spain was not merely a political struggle but encompassed the movement for religious independence from Spain frailocracy. A distinct nationalists church movement gave birth to an independent Filipino church, the Iglesia Filipina Independiente (IFI).